Will Fiscal Policy Be Effective Under EMU? - Cangiano, M. (IMF Working Papers; Working Paper ;, 1998)
European Economic and Monetary Union does not envisage creating a central fiscal authority. Monetary and exchange rate policies will be centralized, but fiscal policy will remain a national responsibility, in line with the subsidiarity principle. This paper argues that monetary union will generate pressures for closer economic integration than currently envisaged. Although not a necessity, a more active central role could then be justified on the grounds of allocative efficiency, redistribution, and stabilization. While in the short term enhanced policy coordination may address those pressures satisfactorily, as economic integration proceeds, the case for a central fiscal authority may become stronger.